Lung abscess by Actinomyces odontolyticus and Parvimonas micra co-infection presenting as acute respiratory failure: A case report. Issue 35 (August 2019) - Yun, Sang Suk; Cho, Hyun Seop; Heo, Manbong; Jeong, Jong Hwan; Lee, Hyang Rae; Ju, Sunmi; Kim, Ju-Young; You, Jung Wan; Cho, Yu Ji; Jeong, Yi Yeong; Kim, Ho Cheol; Lee, Jong Deog; et al.
Abstract: Rationale: Actinomyces odontolyticus and Parvimonas micra are very rare causative organisms of lung abscess and acute respiratory failure. Patient concerns: A 49-year-old male patient visited the emergency room with a complaint of sudden onset of shortness of breath, and he developed acute respiratory failure rapidly. Diagnosis: An abscess in the left lower lung field was diagnosed on the computed tomography scan of chest. Interventions: Immediate treatment with intravenous antibiotics was initiated along with a pigtail catheter insertion for pus drainage. Outcomes: A odontolyticus was cultured on the drained pus and P micra was identified by a blood culture. The patient was successfully weaned from the mechanical ventilator and the lung abscess was completely resolved. Lessons: To the best of our knowledge, this is the first case report of mixed infection with A odontolyticus and P micra, which caused acute respiratory failure in an immune-competent patient. Therefore, physicians should consider the possibility of these organisms as causative pathogens of a fulminant pulmonary infection even in an immune-competent patient.